GaInP/AlGaAs metal‐wrap‐through tandem concentrator solar cells. (28th November 2016) - Oliva, Eduard; Salvetat, Thierry; Jany, Christophe; Thibon, Romain; Helmers, Henning; Steiner, Marc; Schachtner, Michael; Beutel, Paul; Klinger, Vera; Moulet, Jean‐Sebastien; Dimroth, Frank
Abstract: III–V multi‐junction solar cells are promising devices for photovoltaic applications under very high concentration levels of sunlight. Shadowing losses of the front side metallisation and ohmic resistance losses in the metal grid limit the practical cell size typically to around 1 cm 2 at 1000 suns. The use of a full back‐contact architecture, similar to the metal‐wrap‐through (MWT) technology known in silicon photovoltaics, can help to overcome this limitation. Furthermore, positioning both the positive and negative contact pads on the rear side of concentrator solar cells opens the possibility for efficient packaging solutions and the realisation of dense array receivers with low metal shadowing. The MWT technology addresses conventional concentrating photovoltaics as well as combined conventional concentrating photovoltaic‐thermal applications and offers specific advantages for large‐area devices at high intensities. This work presents the first experimental results for MWT architectures applied to III–V tandem solar cells and discusses specific challenges. An efficiency of 28.3% at 176 suns and 27.2% at 800 suns has been measured for the best MWT Ga0.51 In0.49 P/Al0.03 Ga0.97 As tandem solar cells. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The metal‐wrap‐through (MWT) technology addresses conventional concentrating photovoltaics as well as combined photovoltaic thermal application and offers specific advantages for large‐area devices at high intensities. This work presents first experimental result for MWT architectures applied to III–V tandem solar cell and discusses specific challenges. An efficiency of 28.3% at 176 suns 27.2% at 800 suns has been measured for the best MWT GAInP/AIGaAS tandem solar cells.